Bauxite Mining Industry in Guinea and the Valorization Prospects of the Resulting Residue for Engineering Purposes - Diaka Sidibé; Ahmed A. Konaté; Oumar B. Kaba; Sékou Traoré (Novel Perspectives of Engineering Research Vol. 4, 2021)
Guinea is known as a geological scandal due to the importance and diversity of its mineral resources. Experts use superlatives to highlight the country’s bauxite potential, regardless of the assessing system. Several geological surveys agree that Guinea contains 33% of the world’s known bauxite reserves. There is inconsistency in the way the content of a deposit is defined, and the concepts and definitions are mixed up in different statistical data. As a result, an expert comparing various bauxite deposits must recognise the terms in use and adjust them in his assessment for consistency. The vast bauxite potential presents a serious opportunity for the country to become a forerunner in the bauxite and aluminium industries, as well as to develop red mud valorization opportunities. This article discusses the bauxite potential and the local alumina industry in Guinea, as well as the technologies used to value the resulting red mud. The bauxite and alumina sector is responsible for the largest direct contribution to GDP in Guinea.